Colletotrichum species associated with cassava anthracnose in China. Issue 1 (28th November 2018) - Liu, Xianbao; Shi, Tao; Li, Boxun; Cai, Jimiao; Li, Chaoping; Huang, Guixiu
Abstract: Anthracnose caused by Colletotrichum (CAD) is an economically important disease of cassava; however, research on its species diversity and geographical distribution of Colletotrichum in China remains limited. In this study, we investigated the phylogenetic diversity of Colletotrichum isolates associated with symptomatic leaf tissues of cassava from Guangxi and Yunnan provinces in China and aimed to confirm their identification using advanced techniques. Based on multi‐locus phylogenetic analyses and phenotypic characteristics, we identified four species from the isolates, comprising C. plurivorum, C. karstii, C. fructicola and C. siamense, and we found variation in degrees of virulence among the species and between cassava varieties. Our results are the first to report these species from cassava, and they provide a basis for the development of management strategies for CAD in cassava.